A high-durability low-alkali cement and preparation method thereof
The slag is treated by multi-step modification such as sodium lactate, cyclodextrin and flaxseed gel to form a stable complex and modified film, which solves the problem of insufficient strength and frost resistance in the initial hardening of low-alkali cement, and achieves high strength and Durability, maintain low alkali properties, enhance crack and corrosion resistance, and adapt to a wider application environment.
Patent Information
- Application Number
- CN202411070261.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-08-06
AI Technical Summary
The existing low-alkali cement has slow strength development in the early stage of hardening, insufficient anti-freeze performance, and alkaline exciter treatment leads to an increase in alkalinity of the cement system, weakening its crack resistance and stability, and limiting its application range.
The slag is treated with multiple steps such as sodium lactate, cyclodextrin and flaxseed gel to form a stable complex and modified film, activate the active slag, improve early strength and durability, and form a three-dimensional network through sorbitol cross-linking Structure, strengthen the interface transition zone of cement and avoid alkaline increase.
It achieves high strength and durability of low-alkali cement, maintains low-alkali properties, enhances crack resistance and corrosion resistance, adapts to a wider application environment, and improves the overall performance of cement.
Smart Images

Figure CN118812178B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement manufacturing, and in particular to a high-durability low-alkali cement and a preparation method thereof. Background Art
[0002] Since the implementation of the Railway Concrete Engineering Construction Quality Acceptance Standard (TB10424-2018) railway engineering construction standard on February 1, 2019, the relevant standards for related construction materials have been improved and improved, and the product quality requirements for suppliers of related construction materials have also been strengthened. As a new type of cement, low-alkali cement is characterized by a low alkali content. Compared with traditional high-alkali cement, low-alkali cement has better durability, stability and corrosion resistance. It has been widely used in high-speed rail construction. It is widely used in the construction of infrastructure such as bridges, tunnels, and roadbeds. Because of its excellent durability and stability, it can improve the quality and life of high-speed rail infrastructure, reduce the frequency of maintenance and replacement, and thus save costs and resources. Therefore, low-alkali high-speed iron cement can better meet the needs of high-speed rail construction.
[0003] The manufacturing process of low-alkali cement, as a technology dedicated to improving the performance and environmental protection of building materials, has one of its core strategies to cleverly introduce blast furnace slag as a key additive in the traditional cement batching system. Blast furnace slag, as a by-product of the steel industry, is rich in active oxides such as silicon and aluminum. By mixing with cement clinker and an appropriate amount of gypsum and other raw materials, calcining or grinding them, it can not only significantly reduce the alkali content in cement and reduce the risk of concrete alkali-aggregate reaction caused by high-alkali environment, thereby effectively inhibiting the formation of concrete cracks, but also help to recycle resources and reduce waste emissions. However, the high inert components of slag lead to slow strength development of cement in the early stage of hardening, which is undoubtedly a challenge for engineering applications that require rapid achievement of design strength. Secondly, the addition of slag may also affect the frost resistance of cement, making concrete in cold areas or in winter more susceptible to damage from freeze-thaw cycles. Furthermore, the adverse effect of slag on the workability of cement may increase the difficulty of construction and affect the uniformity and density of concrete. The solution in the existing technology is to use alkali activation to treat slag, activate the potential active components in the slag through alkali activators, promote the chemical reaction between it and cement clinker, and then improve the early strength, durability and corrosion resistance of concrete. However, although the use of alkali activators can bring the above advantages, it is also accompanied by the disadvantage of a significant increase in the alkalinity of the cement system, which may not only weaken the original crack resistance and stability advantages of low-alkali cement, but also may cause new chemical erosion problems. At the same time, the decline in strength in the later stage also limits its scope of application. Summary of the invention
[0004] Based on the problems existing in the background technology, the present invention provides a high-durability low-alkali cement and a preparation method thereof. The low-alkali cement has low alkalinity, high strength and good durability.
[0005] The present invention is implemented by the following technical solutions:
[0006] The invention discloses a high-durability low-alkali cement, which comprises the following raw materials in parts by weight: 75-90 parts of low-alkali cement clinker, 5-15 parts of desulfurized gypsum and 15-30 parts of modified slag powder.
[0007] Furthermore, the low-alkali cement clinker includes the following raw materials in parts by weight: 80-90 parts of low-alkali limestone, 5-8 parts of silica tailings, 5-10 parts of fly ash, 3-8 parts of iron ore, and 1-3 parts of steel slag.
[0008] Furthermore, in the low-alkali limestone, by mass fraction, CaO ≥ 49.5%, MgO ≤ 3%, R 2 O≤0.22%, R 2 O is the alkali content, in terms of mNa 2 O+0.658mK 2 O calculation;
[0009] Calculated by mass fraction, SiO 2 ≥90.5%, R 2 O≤0.5%;
[0010] In fly ash, Al 2 O 3 ≥24%, R 2 O≤1.1%, SO 3 ≤1.5%;
[0011] In iron ore, Fe 2 O 3 ≥18%, R 2 O≤1.3%;
[0012] In steel slag, by mass fraction, CaO ≥ 30%, Fe 2 O 3 ≥18%,SiO 2 ≥15%, R 2 O≤1.5%.
[0013] Furthermore, the preparation method of low-alkali cement clinker is specifically as follows: mixing and grinding raw materials to obtain raw materials, calcining the raw materials, and cooling to obtain low-alkali cement clinker; wherein the calcination temperature is 1250-1350°C, and the calcination time is 30-40min.
[0014] Furthermore, the preparation method of modified slag powder comprises the following steps:
[0015] S1. Prepare sodium lactate solution, disperse the slag powder in the sodium lactate solution, stir and mix well, keep for at least 12h, filter and dry to obtain pretreated slag powder;
[0016] S2. Prepare a cyclodextrin solution and a flaxseed gum solution, disperse the pretreated slag powder in the cyclodextrin solution, stir and mix thoroughly, keep for at least 4 hours, filter and dry slightly, and then disperse in the flaxseed gum solution, stir and mix thoroughly, keep for at least 4 hours, filter and dry to obtain a composite treated slag powder;
[0017] S3. Prepare a sorbitol solution, disperse the composite treated slag powder in the sorbitol solution, stir and mix thoroughly for at least 6 hours, filter and dry to obtain modified slag powder.
[0018] Furthermore, in step S1, the slag powder comprises the following components by weight percentage: SiO 2 : 35.24%, Al 2 O 3 :14.30%,Fe 2 O 3 :0.85%, CaO: 37.69%, MgO: 8.54%, K 2 O: 0.60%, Na 2 O:0.23%.
[0019] Further, the concentration of the sodium lactate solution in step S1 is 2-4wt%;
[0020] In step S2, the concentration of the cyclodextrin solution is 1-2wt%, and the concentration of the flaxseed gum solution is 0.5-1wt%;
[0021] The concentration of the sorbitol solution in step S3 is 2-3 wt %.
[0022] The invention also discloses a preparation method of the high-durability low-alkali cement, which specifically comprises the following steps: weighing low-alkali cement clinker, desulfurized gypsum and modified slag powder by weight, adding the powder to a grinding device, and grinding the cement to a fineness of 40-80 μm to obtain the low-alkali cement.
[0023] Furthermore, the grinding device comprises a grinding barrel, a feed port is arranged at the top of the grinding barrel, a grinding unit is arranged in the grinding barrel, and the grinding unit is used to grind the raw materials entering the grinding device into powder;
[0024] The grinding unit includes a conical grinding roller and a grinding base. The grinding base is arranged on the inner wall in the middle of the grinding barrel. A grinding hole is opened at the upper part of the grinding base at a position corresponding to the conical grinding roller. The conical grinding roller is rotatably arranged in the grinding hole. A spiral grinding strip is arranged on the conical surface of the conical grinding roller. The cross section of the grinding strip is semicircular, and the radius of the cross section of the grinding strip gradually decreases from top to bottom.
[0025] Furthermore, the grinding device also includes an airflow separation unit, which includes a separation bin arranged at the bottom of the grinding barrel, a feed inlet is opened on the top surface of the separation bin, the feed inlet is connected with the grinding hole through a receiving barrel, an air inlet is opened on the side wall of the separation bin close to the feed inlet, a fan is arranged outside the air inlet, and a partition is arranged on the bottom surface of the separation bin, which separates the separation bin into a storage area and a return area.
[0026] The grinding device also includes a real-time automatic control system, which is composed of a data acquisition module, a data transmission module, a data processing module, a control instruction execution module and a remote real-time monitoring module.
[0027] The data acquisition module includes a speed sensor of each raw material feeding belt motor and an electronic belt scale metering sensor. The speed sensor of the electric feeding belt motor is used to monitor the working speed of the feeding motor; the electronic belt scale metering sensor is used to monitor the proportion of each material.
[0028] The data processing module stores the collected data in a database and uses the collected data for modeling and simulation: building a large system operation model, analyzing the real-time system operation data, identifying abnormal situations and trends, and adaptively adjusting the control strategy.
[0029] The control instruction execution module includes an industrial controller PLC, a frequency converter and a raw material valve. After receiving the decision instruction of the large model, the industrial controller PLC transmits it to the frequency converter, thereby controlling the speed of the feeding belt motor and the opening of the raw material tank valve to accurately control the ratio of each raw material.
[0030] The remote real-time monitoring module includes a real-time monitoring function, which displays the equipment operating parameters and status in real time; an alarm function, which automatically triggers an alarm and sends a notification when the equipment operating parameters exceed the preset range; and a data visualization function, which displays the system's operating historical data and analysis results through charts and reports.
[0031] Beneficial effects of the present invention:
[0032] 1. The present invention aims to solve the problem in the prior art that the alkalinity of the cement system increases significantly when slag is directly treated with an alkali activator, optimizes the slag treatment method, ensures the overall low alkali content of the cement, and ensures long-term durability and crack resistance. At the same time, it greatly increases the strength of low-alkali cement, and has a good application prospect.
[0033] 2. In the present invention, sodium lactate is first used to perform alkaline excitation on the slag. The carboxyl group (-COOH) in the sodium lactate molecule can react with the metal ions (such as Ca 2+ 、Al 3+ The slag is treated with cyclodextrin and linseed gum, and cyclodextrin can protect and activate the active sites on the surface of slag and enhance its volcanic ash reactivity. Linseed gum has good adhesion and film-forming properties, and interacts with the surface of slag treated with cyclodextrin to form a stable coating, further improving the dispersibility and wettability of slag and enhancing the compatibility of slag with other components. Through the composite treatment of cyclodextrin and linseed gum, a stable modified film is formed on the slag surface to improve its surface activity and dispersibility. Finally, it is treated with sorbitol to form a stable three-dimensional network structure on the slag surface through the cross-linking reaction of sorbitol. Through multi-step modification, slag forms a better interface transition zone in the cement matrix, improving the overall durability of the cement and adapting to a wider range of application environments.
[0034] 3. The present invention also optimizes the cement grinding process by using grinding bars whose radius gradually decreases from top to bottom. During the grinding process, the grinding space gradually becomes smaller, so that the raw materials can be gradually ground to a smaller fineness. The grinding efficiency is high, and the airflow separation can achieve cement powder with a qualified fineness. Compared with the traditional screening method, it has high efficiency and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The accompanying drawings are used to provide further explanation of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0036] Figure 1 It is a schematic structural diagram of the grinding device disclosed in the present invention;
[0037] Figure 2 for Figure 1 An enlarged view of part A;
[0038] Figure 3 It is a schematic structural diagram of the conical grinding roller disclosed in the present invention. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the following embodiments.
[0040] The raw materials and their chemical compositions (%) used in the examples and comparative examples of the present invention are shown in Table 1.
[0041] Table 1
[0042] name LOI <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> CaO MgO <![CDATA[SO 3 ]]> <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> Low Alkali Limestone 42.33 2.79 0.50 1.32 49.72 2.67 0.01 0.30 0.04 Silica tailings 0.39 93.88 2.57 1.05 0.35 0.12 0.01 0.26 0.20 Fly ash 4.56 47.32 30.50 6.19 6.54 2.06 1.17 0.79 0.48 Iron Ore 0.73 63.14 5.01 20.69 4.30 3.27 0.25 0.98 0.59 Steel slag 0.00 16.35 7.13 20.27 45.02 7.06 0.21 0.06 0.10 slag 0.00 35.24 14.30 0.85 37.69 8.54 1.68 0.60 0.23
[0043] Example 1
[0044] The preparation of high-durability low-alkali cement comprises the following steps:
[0045] (1) Preparation of low-alkali cement clinker
[0046] Weigh low-alkali cement clinker raw materials: 85 parts by weight of low-alkali limestone, 6 parts of silica tailings, 8 parts of fly ash, 5 parts of iron ore, and 2 parts of steel slag, mix and grind the raw materials to obtain raw meal, calcine the raw meal, and cool it to obtain low-alkali cement clinker; wherein the calcination temperature is 1300°C and the calcination time is 30 min.
[0047] (2) Preparation of modified slag powder
[0048] The preparation method comprises the following steps:
[0049] S1. Prepare a sodium lactate solution with a concentration of 3wt%, disperse the slag powder in the sodium lactate solution at a solid-liquid ratio of 1:3, stir and mix thoroughly, keep for at least 12h, filter and dry to obtain pretreated slag powder;
[0050] S2. Prepare a cyclodextrin solution with a concentration of 1.2wt% and a flaxseed gum solution with a concentration of 0.6wt%, disperse the pretreated slag powder in the cyclodextrin solution at a solid-liquid ratio of 1:5, stir and mix thoroughly, keep for at least 4 hours, filter and dry slightly, and then disperse in the flaxseed gum solution at a solid-liquid ratio of 1:5, stir and mix thoroughly, keep for at least 4 hours, filter and dry to obtain composite treated slag powder;
[0051] S3. Prepare a 2.5wt% sorbitol solution, disperse the composite treated slag powder in the sorbitol solution at a solid-liquid ratio of 1:5, stir and mix thoroughly, keep for at least 6 hours, filter and dry to obtain modified slag powder.
[0052] (3) Preparation of low-alkali cement
[0053] 85 parts of low-alkali cement clinker, 10 parts of desulfurized gypsum and 20 parts of modified slag powder were weighed by weight, added into a grinding device, and the cement was ground to a fineness of 40-80 μm to obtain low-alkali cement.
[0054] Example 2
[0055] The preparation of high-durability low-alkali cement comprises the following steps:
[0056] (1) Preparation of low-alkali cement clinker
[0057] Same as Example 1.
[0058] (2) Preparation of modified slag powder
[0059] The preparation method comprises the following steps:
[0060] S1. Prepare a sodium lactate solution with a concentration of 2.5wt%, disperse the slag powder in the sodium lactate solution at a solid-liquid ratio of 1:3, stir and mix thoroughly, keep for at least 12h, filter and dry to obtain pretreated slag powder;
[0061] S2. Prepare a cyclodextrin solution with a concentration of 1wt% and a flaxseed gum solution with a concentration of 0.8wt%, disperse the pretreated slag powder in the cyclodextrin solution at a solid-liquid ratio of 1:5, stir and mix thoroughly, keep for at least 4 hours, filter and dry slightly, and then disperse in the flaxseed gum solution at a solid-liquid ratio of 1:5, stir and mix thoroughly, keep for at least 4 hours, filter and dry to obtain composite treated slag powder;
[0062] S3. Prepare a 2 wt% sorbitol solution, disperse the composite treated slag powder in the sorbitol solution at a solid-liquid ratio of 1:5, stir and mix thoroughly for at least 6 hours, filter and dry to obtain modified slag powder.
[0063] (3) Preparation of low-alkali cement
[0064] Same as Example 1.
[0065] Example 3
[0066] The preparation of high-durability low-alkali cement comprises the following steps:
[0067] (1) Preparation of low-alkali cement clinker
[0068] Same as Example 1.
[0069] (2) Preparation of modified slag powder
[0070] Same as Example 1.
[0071] (3) Preparation of low-alkali cement
[0072] Weigh 85 parts of low-alkali cement clinker, 10 parts of desulfurized gypsum, and 25 parts of modified slag powder by weight, add them into a grinding device, and grind the cement to a fineness of 40-80 μm to obtain low-alkali cement.
[0073] Comparative Example 1
[0074] The preparation of low-alkali cement comprises the following steps:
[0075] (1) Preparation of low-alkali cement clinker
[0076] Same as Example 1.
[0077] (2) Slag powder treatment
[0078] A sodium lactate solution with a concentration of 2.5 wt% is prepared, and the slag powder is dispersed in the sodium lactate solution at a solid-liquid ratio of 1:3. After being fully stirred and mixed, the mixture is maintained for at least 12 hours, filtered and dried to obtain the treated slag powder.
[0079] (3) Preparation of low-alkali cement
[0080] Weigh 85 parts of low-alkali cement clinker, 10 parts of desulfurized gypsum, and 20 parts of treated slag powder by weight, add them into a grinding device, and grind the cement to a fineness of 40-80 μm to obtain low-alkali cement.
[0081] Comparative Example 2
[0082] The preparation of low-alkali cement comprises the following steps:
[0083] (1) Preparation of low-alkali cement clinker
[0084] Same as Example 1.
[0085] (2) Preparation of modified slag powder
[0086] The preparation method comprises the following steps:
[0087] S1. Prepare a sodium lactate solution with a concentration of 2.5wt%, disperse the slag powder in the sodium lactate solution at a solid-liquid ratio of 1:3, stir and mix thoroughly, keep for at least 12h, filter and dry to obtain pretreated slag powder;
[0088] S2. Prepare a cyclodextrin solution with a concentration of 1wt% and a flaxseed gum solution with a concentration of 0.8wt%, disperse the pretreated slag powder in the cyclodextrin solution at a solid-liquid ratio of 1:5, stir and mix thoroughly, keep it for at least 4 hours, filter and dry slightly, then disperse it in the flaxseed gum solution at a solid-liquid ratio of 1:5, stir and mix thoroughly, keep it for at least 4 hours, filter and dry to obtain modified slag powder.
[0089] (3) Preparation of low-alkali cement
[0090] Weigh 85 parts of low-alkali cement clinker, 10 parts of desulfurized gypsum, and 20 parts of treated slag powder by weight, add them into a grinding device, and grind the cement to a fineness of 40-80 μm to obtain low-alkali cement.
[0091] Comparative Example 3
[0092] The preparation of low-alkali cement comprises the following steps:
[0093] (1) Preparation of low-alkali cement clinker
[0094] Same as Example 1.
[0095] (2) Preparation of modified slag powder
[0096] The preparation method comprises the following steps:
[0097] S1. Prepare a sodium lactate solution with a concentration of 3wt%, disperse the slag powder in the sodium lactate solution at a solid-liquid ratio of 1:3, stir and mix thoroughly, keep for at least 12h, filter and dry to obtain pretreated slag powder;
[0098] S2. Prepare a cyclodextrin solution with a concentration of 1.2 wt%, disperse the pretreated slag powder in the cyclodextrin solution at a solid-liquid ratio of 1:5, stir and mix thoroughly, keep for at least 4 hours, filter and dry to obtain cyclodextrin-treated slag powder;
[0099] S3. Prepare a 2.5wt% sorbitol solution, disperse the cyclodextrin treated slag powder in the sorbitol solution at a solid-liquid ratio of 1:5, stir and mix thoroughly for at least 6 hours, filter and dry to obtain modified slag powder.
[0100] (3) Preparation of low-alkali cement
[0101] Weigh 85 parts of low-alkali cement clinker, 10 parts of desulfurized gypsum, and 20 parts of treated slag powder by weight, add them into a grinding device, and grind the cement to a fineness of 40-80 μm to obtain low-alkali cement.
[0102] Test Example 1
[0103] The physical and chemical properties of the low-alkali cement product prepared in Example 1 of the present invention were tested, and the results met the index requirements of GB175-2007 and TB10424-2018 at the same time. The results are shown in Table 2.
[0104] Table 2
[0105]
[0106]
[0107] Test Example 2
[0108] The low-alkali cement prepared in Examples 1-3 and Comparative Examples 1-4 of the present invention was respectively used in concrete, and the performance of the concrete was tested. The test standards were as follows:
[0109] Sulfate corrosion resistance test: The test is carried out according to the immersion corrosion resistance test method (K method) in GB / T749-2008 "Test method for sulfate corrosion resistance of cement". Under normal circumstances, when the corrosion resistance coefficient K ≥ 0.8, the corrosion resistance is qualified; when K < 0.8, the corrosion resistance is unqualified and the specimen is considered to be damaged by corrosion;
[0110] Chloride ion corrosion resistance test: The chloride ion diffusion coefficient of concrete is tested according to the rapid chloride ion migration coefficient method (RCM method) in GB / T50082-2009 "Standard for test methods of long-term performance and durability of ordinary concrete";
[0111] Crack resistance (crack resistance grade): JGJ / T193-2009, grade classification LI (total cracking area per unit area ≥ 1000mm 2 / m 2 )、L-II(1000mm 2 / m 2 >Total cracking area per unit area ≥700mm 2 / m 2 )、L-III(700mm 2 / m 2 >Total cracking area per unit area ≥400mm 2 / m 2 )、L-IV(400mm 2 / m 2 >Total cracking area per unit area ≥100mm 2 / m 2 ), LV (total cracking area per unit area <100mm 2 / m 2 ), the higher the grade, the better the crack resistance;
[0112] Frost resistance (mass loss rate of D50 freeze-thaw test): JC475-2004, a frost resistance lower than 3% is excellent frost resistance.
[0113] The test results are shown in Table 3.
[0114] Table 3
[0115]
[0116] As can be seen from the results in Table 3, the concrete prepared by low-alkali cement in Examples 1-3 has better erosion resistance, corrosion resistance and high durability. The inclusion complex of cyclodextrin and the sticky coating of linseed gum improve the dispersibility of slag in cement, avoid the aggregation of particles, and contribute to uniform hydration. The composite-treated slag forms a better interface transition zone in the cement matrix, reduces the generation of microcracks, improves the density and freeze-thaw resistance of the material, and reduces the chloride ion diffusion coefficient. Sorbitol cross-linking can form a stable network structure, improve the stability and durability of the slag coating, improve the corrosion resistance of cement, further reduce the penetration and expansion pressure of water, and reduce the chloride ion diffusion coefficient. In addition, the cross-linked slag surface coating has higher flexibility and strength, and can effectively absorb and disperse external forces to reduce the generation and expansion of cracks. In a word, through multi-step modification, slag forms a better interface transition zone in the cement matrix, improves the overall durability of cement, and adapts to a wider range of application environments.
[0117] Example 4
[0118] like Figure 1-3 As shown, the grinding device includes a grinding barrel 1, a feed port 2 is arranged at the top of the grinding barrel 1, and a grinding unit is arranged inside the grinding barrel 1, and the grinding unit is used to grind the raw materials entering the grinding device into powder;
[0119] The grinding unit includes a conical grinding roller 3 and a grinding base 4. The grinding base 4 is arranged on the inner wall in the middle of the grinding barrel 1. A grinding hole 5 is opened at the upper part of the grinding base 4 at a position corresponding to the conical grinding roller 3. The conical grinding roller 3 is rotatably arranged in the grinding hole 5. A spiral grinding strip 6 is arranged on the conical surface of the conical grinding roller 3. The cross section of the grinding strip 6 is semicircular, and the radius of the cross section of the grinding strip 6 gradually decreases from top to bottom.
[0120] The grinding device also includes an air flow separation unit, which includes a separation bin 7 arranged at the bottom of the grinding barrel 1, a feed port 8 is opened on the top surface of the separation bin 7, the feed port 8 is connected with the grinding hole 5 through a receiving barrel 9, an air inlet 18 is opened on the side wall of the separation bin 7 close to the feed port 8, a fan 10 is arranged outside the air inlet 18, and a partition 11 is arranged on the bottom surface of the separation bin 7, and the partition 11 separates the separation bin 7 into a storage area 12 and a return area 13.
[0121] The working principle and beneficial effects of the above technical solution are as follows: the raw materials weighed by weight are added into the grinding barrel 1 from the feed port 2; the upper surface of the grinding base 4 is a downwardly concave cone; the grinding base 4 is fixedly arranged on the inner wall of the middle part of the grinding barrel 1 and is sealed with the grinding barrel 1; the raw materials enter the gap between the grinding roller 3 and the grinding hole 5 from the conical upper surface of the grinding base 4; the motor 17 drives the grinding roller 3 to rotate through the transmission shaft 16; the grinding strip 6 grinds the raw materials between the grinding roller 3 and the grinding hole 5 into powder, and enters the receiving barrel 9 from the lower end of the grinding hole 5; the raw materials enter ... The strips 6 are in contact with the grinding hole 5 and are pressed tightly, so that the raw materials between the grinding roller 3 and the grinding hole 5 can be ground into powder. The radius of the grinding strips 6 gradually decreases from top to bottom, so that the gap between the grinding roller 3 and the grinding hole 5 gradually decreases upward. During the grinding process, the raw materials are gradually ground from a larger size to a smaller size until the fineness reaches the requirements of the finished cement. During the grinding process, the grinding roller 3 rotates counterclockwise (as viewed from above the grinding roller), and the spiral outer edge of the grinding roller can also discharge the ground cement powder downward. A plurality of grinding strips 6 can be arranged in an array along the circumferential direction of the grinding roller 3.
[0122] The upper part of the material receiving barrel 9 is cylindrical, and the upper end is connected to the grinding hole 5. The lower part of the material receiving barrel 9 is rectangular cylindrical. The shape of the feeding port 8 is adapted to the rectangular cylindrical shape of the lower part of the material receiving barrel 9. The middle part of the material receiving barrel 9 is a transition section. The upper end is fixedly connected and communicated with the cylindrical shape of the upper part of the material receiving barrel 9, and the lower part is fixedly connected and communicated with the upper end of the rectangular cylindrical shape of the lower part of the material receiving barrel 9. After the cement raw material is ground into powder, it enters the separation bin 7 from the feeding port 8. During the falling process, it is blown by the airflow transported to the separation bin 7 by the fan 10 through the air inlet 18. Under the action of the airflow, the finer the cement powder, the farther it is blown. The powdered cement with a fineness that meets the requirements of the cement finished product is blown to the storage area 12 farther from the air inlet 18. A discharge port 14 is opened at the bottom of the storage area 12. The height of the partition 11 is less than the height of the separation bin 7, and the height of the top surface of the partition 11 is consistent with the height of the lower edge of the air inlet 18. The part of cement that cannot meet the requirements of finished cement fineness will fall into the return area 13. The lower part of the return area 13 is provided with a return unit 15 connected with the upper part of the grinding barrel 1, and the cement with unqualified fineness is returned to the upper part of the grinding unit for grinding again. The return unit is a prior art, such as the return mechanism recorded in CN220780649U, which will not be repeated here.
[0123] The grinding barrel 1 is sealed, and sealing valves are provided on the feed inlet 2 and the discharge port 14 to prevent cement powder from leaking during the grinding and separation process.
[0124] The grinding bar with radius gradually decreasing from top to bottom is adopted. During the grinding process, the grinding space gradually becomes smaller, so that the raw materials can be gradually ground to a smaller fineness. The grinding efficiency is high, and the airflow separation can achieve cement powder with qualified fineness. Compared with the traditional screening method, it has high efficiency and low cost.
[0125] Example 5
[0126] The grinding device also includes a real-time automatic control system, which is composed of a data acquisition module, a data transmission module, a data processing module, a control instruction execution module and a remote real-time monitoring module.
[0127] The data acquisition module includes a speed sensor of each raw material feeding belt motor and an electronic belt scale metering sensor. The speed sensor of the electric feeding belt motor is used to monitor the working speed of the feeding motor; the electronic belt scale metering sensor is used to monitor the proportion of each material.
[0128] The data processing module stores the collected data in a database and uses the collected data for modeling and simulation: building a large system operation model, analyzing the real-time system operation data, identifying abnormal situations and trends, and adaptively adjusting the control strategy.
[0129] The control instruction execution module includes an industrial controller PLC, a frequency converter and a raw material valve. After receiving the decision instruction of the large model, the industrial controller PLC transmits it to the frequency converter, thereby controlling the speed of the feeding belt motor and the opening of the raw material tank valve to accurately control the ratio of each raw material.
[0130] The remote real-time monitoring module includes a real-time monitoring function, which displays the equipment operating parameters and status in real time; an alarm function, which automatically triggers an alarm and sends a notification when the equipment operating parameters exceed the preset range; and a data visualization function, which displays the system's operating historical data and analysis results through charts and reports.
[0131] When the grinding equipment starts working, the valves of each raw material tank are opened at a preset opening, and the feeding motor starts working at a set speed. The weight display of each raw material on the electronic belt scale is monitored in real time and compared with the ratio setting value in real time. When an error occurs, the system runs a large model for real-time analysis, self-learns and adjusts parameters, and transmits the analysis results to the industrial controller PLC. The industrial controller PLC then transmits instructions to the valves of each raw material tank and the inverter to control the supply amount of each raw material, thereby accurately controlling the ratio of each raw material.
[0132] The real-time automatic control system of the grinding equipment can realize comprehensive monitoring and intelligent management of the raw material ratio, improve accuracy, increase production efficiency, reduce labor costs, and ensure stable operation of the equipment.
[0133] Finally, it should be noted that the above-mentioned embodiments only express several implementation methods of the present invention and are not intended to limit the invention. For ordinary technicians in this field, any modifications, equivalent substitutions, improvements, etc. made without departing from the concept of the present invention should be included in the protection scope of the invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.
Claims
1. A high-durability low-alkali cement, characterized in that: The raw materials include the following parts by weight: 75-90 parts of low-alkali cement clinker, 5-15 parts of desulfurized gypsum, and 15-30 parts of modified slag powder; The preparation method of the modified slag powder comprises the following steps: S1. Prepare sodium lactate solution, disperse the slag powder in the sodium lactate solution, stir and mix well, keep for at least 12h, filter and dry to obtain pretreated slag powder; S2. Prepare a cyclodextrin solution and a flaxseed gum solution, disperse the pretreated slag powder in the cyclodextrin solution, stir and mix thoroughly, keep for at least 4 hours, filter and dry slightly, and then disperse in the flaxseed gum solution, stir and mix thoroughly, keep for at least 4 hours, filter and dry to obtain a composite treated slag powder; S3. Prepare a sorbitol solution, disperse the composite treated slag powder in the sorbitol solution, stir and mix well, keep for at least 6h, filter and dry to obtain a modified slag powder; The concentration of the sodium lactate solution in step S1 is 2-4wt%; In step S2, the concentration of the cyclodextrin solution is 1-2wt%, and the concentration of the flaxseed gum solution is 0.5-1wt%; The concentration of the sorbitol solution in step S3 is 2-3 wt %.
2. The high-durability low-alkali cement according to claim 1, characterized in that: The low-alkali cement clinker comprises the following raw materials in parts by weight: 80-90 parts of low-alkali limestone, 5-8 parts of silica tailings, 5-10 parts of fly ash, 3-8 parts of iron ore, and 1-3 parts of steel slag.
3. The high-durability low-alkali cement according to claim 2, characterized in that: In low-alkali limestone, by mass fraction, CaO ≥ 49.5%, MgO ≤ 3%, R2O ≤ 0.22%, R2O is the alkali content, calculated as mNa2O + 0.658mK2O; In silica tailings, SiO2≥90.5% and R2O≤0.5% by mass fraction; In fly ash, Al2O3≥24%, R2O≤1.1%, SO3≤1.5% by mass fraction; In iron ore, by mass fraction, Fe2O3≥18%, R2O≤1.3%; Calculated by mass fraction, CaO ≥ 30%, Fe2O3 ≥ 18%, SiO2 ≥ 15%, and R2O ≤ 1.5% in steel slag.
4. The high-durability low-alkali cement according to claim 2, characterized in that: The preparation method of low-alkali cement clinker is specifically as follows: mixing and grinding raw materials to obtain raw materials, calcining the raw materials, and cooling to obtain low-alkali cement clinker; wherein the calcination temperature is 1250-1350°C, and the calcination time is 30-40min.
5. The high-durability low-alkali cement according to claim 1, characterized in that: In step S1, the slag powder contains the following components by weight percentage: SiO2: 35.24%, Al2O3: 14.30%, Fe2O3: 0.85%, CaO: 37.69%, MgO: 8.54%, K2O: 0.60%, and Na2O: 0.23%.
6. A method for preparing high-durability low-alkali cement according to any one of claims 1 to 5, characterized in that: The specific operation is: weigh low-alkali cement clinker, desulfurized gypsum and modified slag powder according to weight, add them into a grinding device, and grind the cement to a fineness of 40-80μm to obtain low-alkali cement.
7. The method for preparing high-durability low-alkali cement according to claim 6, characterized in that: The grinding device comprises a grinding barrel (1), a feed inlet (2) is arranged at the top of the grinding barrel (1), and a grinding unit is arranged inside the grinding barrel (1), and the grinding unit is used to grind the raw materials entering the grinding device into powder; The grinding unit comprises a conical grinding roller (3) and a grinding base (4); the grinding base (4) is arranged on the inner wall of the middle part of the grinding barrel (1); a grinding hole (5) is provided at a position on the upper part of the grinding base (4) corresponding to the conical grinding roller (3); the conical grinding roller (3) is rotatably arranged in the grinding hole (5); a spiral grinding strip (6) is arranged on the conical surface of the conical grinding roller (3); the cross section of the grinding strip (6) is semicircular; and the radius of the cross section of the grinding strip (6) gradually decreases from top to bottom.
8. The method for preparing high-durability low-alkali cement according to claim 6, characterized in that: The grinding device further comprises an air flow separation unit, which comprises a separation bin (7) arranged at the bottom of the grinding barrel (1), a material inlet (8) being provided on the top surface of the separation bin (7), the material inlet (8) being connected to the grinding hole (5) through a material receiving barrel (9), an air inlet (18) being provided on the side wall of the separation bin (7) close to the material inlet (8), a fan (10) being provided outside the air inlet (18), and a partition (11) being provided on the bottom surface of the separation bin (7), the partition (11) dividing the separation bin (7) into a material storage area (12) and a material return area (13).
